Діагностика частинок у пиловій RF плазмі - Filatova, I.I.; Azharonok, V.V.; Chubrik, N.I.; Malevanova, A.A.; Truhachev, F.M.; Ramazanov, T.S. (Publishing house "Academperiodika", 2022)
We study the dynamics of polydisperse dust particles in a rf post-discharge plasma. The levitation of charged particles after the discharge switching-off is found, and the velocities of their fall are measured. A model of the dynamics of particles in the afterglow plasma is proposed to estimate their size and residual charge.